Et si la Grande Guerre commençait en 1911 ? L’entrée en guerre vue d’Alexandrie - Elena Chiti (Revue des Mondes Musulmans et de la Méditerranée)
Abstract :. This paper aims to contribute to a better understanding of the outbreak of the Great War in the Arab-Ottoman world, by analyzing the ways it was perceived in the city of Alexandria. Perceptions are reconstructed through a study of Alexandrian Arabic literary sources of the time. An approach through the city enables abandoning the anachronistic framework of the nation and giving the imperial horizon the relevance it deserves. This also helps to rethink the chronology. In fact, the weakening of the Ottoman Empire was seen with anxiety, not only since 1914, but after the Italian invasion of Tripoli in 1911. This colonial occupation of an Ottoman province seems to be the real turning point. The ineffectiveness of intra-Ottoman solidarity, in an Egyptian province which was also under foreign occupation, led to a brutal disillusionment. It is not only the imperial horizon, but the world order that loses its meaning, generating the perception of entering into the war.